Maps, Travel and Exploration in the Middle Ages: Some Reflections about Anachronism - Dalché, Patrick Gautier (The Historical Review/La Revue Historique, 2015)
Abstract: How were maps conceived in the Middle Ages? Using the words “map”, “travel” and “exploration”, historians must be wary of anachronism. Medieval maps, like ours maps, are always materialized thought-objects and are thus interpretations of the world, inevitably variable and subject to criticism; in this respect, “modernity” has neither invented nor changed anything. The article addresses some anachronisms about the role of mappae mundi in mental journeys, their function in maritime travels and their role during the great “discoveries”; it claims that no other pre-modern civilization, except perhaps the Chinese, was ever so imbued with cartographic culture.